Advances in understanding and managing Scedosporium respiratory infections in patients with cystic fibrosis. (3rd March 2020) - Bouchara, Jean-Philippe; Le Govic, Yohann; Kabbara, Samar; Cimon, Bernard; Zouhair, Rachid; Hamze, Monzer; Papon, Nicolas; Nevez, Gilles
ABSTRACT: Introduction : Considered for a long time to be exclusively responsible for chronic localized infections, fungi of the genus Scedosporium have recently received a renewed interest because of their recognition as common colonizing agents of the respiratory tract of patients with cystic fibrosis, and of the description of severe disseminated infections in patients undergoing lung transplantation. Recently, several studies have been carried out on these opportunistic pathogens, which led to some advances in the understanding of their pathogenic mechanisms and in the biological diagnosis of the airway colonization/respiratory infections caused by these fungi. Areas covered : From a bibliographic search on the Pubmed database, we summarize the current knowledge about the taxonomy of Scedosporium species, the epidemiology of these fungi and their pathogenic mechanisms, and present the improvements in the detection of the airway colonization and diagnosis of Scedosporium respiratory infections, the difficulties in their therapeutic management, and the antifungal drugs in development. Expert opinion : As described in this review, many advances have been made regarding the taxonomy and ecology of Scedosporium species or the molecular determinants of their pathogenicity, but also in the management of Scedosporium infections, particularly by improving the biological diagnostic and publishing evidence for the efficacy of combined therapy.